Niespełnione nadzieje polityki traktatowej. Upadek systemu wersalskiego z polskiej perspektywy - Kania, Krzysztof (1976– ) (Instytut Historii PAN, 2024)
The article aims to shed new light on the main objectives of European and Polish foreign policy in post-Versailles Europe. In his analysis, the author focuses on the chosen pacts and treaties and shows the Polish perspective. It makes it possible to answer the question: Why did the Paris Peace Treaty of 1919 fail to prevent another global conflict?
p. 155-171
Summary in English.
Keywords: Polish foreign policy; history of diplomac; post-Versailles Europe; Poland - foreign relations; international relations - 1918-1939; pacts and treaties; Treaty of Versailles (1919); Paris Peace Conference (1919/1920); Poland - foreign relations - 1900-1945